Sleep Deprivation and Sleep Quality of Healthcare Shift Workers in Bangladesh - Hossain, Md Salim; Uddin, Muhammad Kamal (Dhaka University Journal of Biological Sciences, 2024)
Shift work is an essential feature of industrialized society. Our present study was aimed at investigating the sleep deprivation and sleep quality of the healthcare shift workers in Bangladesh. In investigating so, we took 462 healthcare shift workers from five districts of Bangladesh. Among them 152 were male and 310 were female. The participants ranged from 19 to 65 years of age. We took the participants on the basis of convenience sampling technique from 30 hospitals and medical centers. To collect data we administered Bangla version of Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS). Findings of our study revealed that sleep deprivation and shifts were marginally dependent (χ2 = 11.56, p = 0.07). However, sleep quality had been found independent of shifts (χ2 = 4.31, p = 0.12). Shift-wise analyses yielded that sleep deprivation was high (μ = 7.56) and sleep quality was worse (μ = 3.78) in rotating shift workers in comparison to fixed and regular shift workers. Sleep quality was found better outside of metropolitan city (t = -3.258, p<0.01). Findings have been discussed in terms of previous findings and contemporary theories. Recommendations are proposed in the light of our findings in conclusion. Dhaka Univ. J. Biol. Sci. 33(2): 67-75, 2024 (July)